PENGEMBANGAN MATERIAL KOMPOSIT TAHAN PANAS DENGAN MENGGUNAKAN METODE 3D PRINTING DAN HAND LAY UP - kiki selo ageng; Ikbal Riski Putra; Sehono (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2023)
Sandwich composites are a combination of two materials that have different properties which are then put together to have stronger properties and resistance than their constituents, consisting of the skin and the core. In this study, ceramic fiber blanket insulation was used, leather fiber, core polylactid acid (PLA) and united using merrhyl polyester resin. This research produces a new composite product with a honeycomb core combined with a core made of PLA which is printed with 3D printing, the manufacturing process is by using a hand lay up based on its superiority which is a simpler process, making heat resistant composites by combining ceramic fiber blanket fibers insulation and merrhyl polyester resin, in the thermal conductivity test and also the impact charpy obtained the results from the impact charpy test with a honeycomb core with a ratio of 50% fiber and 50% resin to get an impact on specimen 3 of 4,848j then on impact without skin only PLA got a value of 1.5034j in the thermal conductivity test with a time of 30s to get a Q1 temperature of 1.3130C in Q2 to get a result of 3540C in this study obtained a heat-resistant composite with a mixture of ceramic fiber blankets this insulating material is suitable for the temperature conditions from the results of this test fix what the impact results and also know the ceramic fiber blanket insulation fiber which is suitable for use in composite materials that require high temperatures.